A Review on Polyherbal Formulations and Herbal Medicine for Management of Ulcer with Recent Trends - Jain, Monika (International Journal of Pharmaceutical & Biological Archive, 2023)
A peptic ulcer (PU) is common gastrointestinal disorder which is seen among many people. It is an erosion in a segment of the gastrointestinal mucosa, typically in the stomach (gastric ulcer) or first few centimeters of duodenum (duodenal ulcer) that penetrates through the muscularis mucosae. Ulceration occurs when there is a disturbance of the normal equilibrium caused by either enhanced aggression or diminished mucosal resistance. It may cause by Helicobacter pylori infection, regular usage of non-steroidal anti-inflammatory’s, irregular food habits, stress, and gastric acid secretions. There are several synthetic medications available to treat ulcers. However, compared to herbal supplements, these medications are more expensive and likely to have more side effects. Various herbal medicines have traditionally been used to cure PU disease. The active phytochemical components of a single plant are insufficient to produce the desired therapeutic effects. Combination of two or more than two herbs is called polyherbal formulation. Polyherbal formulations are used to improve the therapeutic potential. The medicinal effect will be boosted and the toxicity will be reduced when various herbs are combined in appropriate ratios in the polyherbal formulation that this study is based on the herbs, polyherbal formulations (in treating PU), recent work, and patent on polyherbal formulations based on pharmacological activities.